Вплив екологічних і соціально-політичних факторів на генофонд популяції - Служинська, З.; Калинюк, П. (Праці наукового товариства ім. Шевченка, 2001)
Генофонд популяції людини зазнавав не лише впливів суто біотичних та абіотичних факторів, економічного та соціального довкілля, а й політичних чинників, які зумовлюють демографічні коливання. Війни, колективізація, голодомори, масові депортації, що були в минулому України, призвели до зміни генофонду популяції людей. До того треба додати воєнні втрати і масові вбивства більшовицькими і фашистськими окупантами мирного населенням. Усе це створює довкілля, яке
пролонговано змінює духовні та моральні властивості людей. Genetic population possesses certain gene pool and exists in time and space. Continuity in time is ensured by reproductive links between generations. Continuity in space, i.e. single territory, is ensured by panmixia inside population. Self-reproduction of population gene pool in the next generation is possible only provided that all the members of population take part in reproduction process. Populations are created under certain historical, cultural, economic and property conditions. Social factors form ethnical groups, which contribute to the economy of society. Destruction of population is highly undesirable phenomenon. It leads to disharmony both inside ethnic groups and state economic structure. Population exists within certain limits of historical time and geographical space.